The Realization of Centralized Server User Interface for Network Communication and Control of Devices for Partial Discharge Monitoring - Cakić, Nikola S; Cakić, Milica; Žigić, Aleksandar; Milosavljević, Srđan; Kartalović, Nenad (Proceedings, Electrical engineering institute "Nikola Tesla", 2018)
This paper presented a centralized solution for network communication and control of remote devices for partial discharge monitoring. Java SWT server application (user interface) was realized for that solution. Server user interface has the role to replace remote desktop in the local network. The remote desktop was replaced because of the limitations imposed by the extension of the monitoring system. As the monitoring system for partial discharge was installed on five more generators, there was a need to centralize data on server computer with VPN server application. The server user interface is located on central VPN server and communicates with Java SWT client applications on local computers. The partial discharge monitoring software runs on local computers. All relevant information for end user are transmitted using server-client connection. The server user interface has two access levels: administrator and user. Depending on the access level it is possible either only to observe monitoring parameters or changing parameters and giving commands.